2007
DOI: 10.1002/arch.20181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ecdysteroid agonist RH‐2485 reveal interactions between ecdysteroids and juvenile hormones in the development of Sesamia nonagrioides

Abstract: Larvae of Sesamia nonagrioides developing under long day (LD) conditions pupate in the 5th or 6th instar, whereas under the short day (SD) conditions, they undergo several supernumerary larval molts and are regarded as diapausing. The development in early larval instars occurs in the LD larvae at a moderate and in the SD larvae at a high juvenile hormone (JH) titer; ecdysteroid titer cycles similarly under both conditions. The transformation to pupa is initiated by a burst of ecdysteroids at undetectable JH le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
2
16
0
1
Order By: Relevance
“…Thus, the insects molted to nonviable forms between the life stages (Tateishi et al 1993). Molts induced during the early phase of the last instar produce larval-like individuals, while those formed in the late phase generate pupal-like individuals (Eizaguirre et al 2007), as was observed in our study.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Thus, the insects molted to nonviable forms between the life stages (Tateishi et al 1993). Molts induced during the early phase of the last instar produce larval-like individuals, while those formed in the late phase generate pupal-like individuals (Eizaguirre et al 2007), as was observed in our study.…”
Section: Discussionsupporting
confidence: 83%
“…It is documented that ecdysone agonists cause larvae to stop feeding, what leads to a reduced larval body weight (Pineda et al 2006, Eizaguirre et al 2007. In our study, the effect of methoxyfenozide on pupal weight was dose-dependent and more pronounced in females than in males.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…The ecdysteroids titer rose before each extra larval moult in S. nonagrioides and a burst at the passing 8 th to 9 th instar (Eizaguirre et al. , 2007) that is at day 60 of our collection time (Fantinou et al.…”
Section: Discussionmentioning
confidence: 99%
“…The high effectiveness of methoxyfenozide against lepidopteran larvae when exposed, either through topical application or by ingestion, has been widely recognized (Pineda et al ., ; Eizaguirre et al ., ; Rodríguez et al ., ). One of the reasons for the efficacy of ecdysone agonists is their rather high foliar stability.…”
Section: Introductionmentioning
confidence: 98%